Factors that prevent, prompt, and delay disclosures in female victims of child sexual abuse. (March 2020) - Kellogg, Nancy D.; Koek, Wouter; Nienow, Shalon M.
Abstract: Background: Several studies conducted in clinical and non-clinical settings have described why and when children disclose sexual abuse. Yet, there is incomplete understanding of how adolescents and young children may differ in factors that delay, prompt and deter disclosure that could inform strategies for clinical practice and prevention. Objective: The aim of this study was to identify factors that prevent, prompt, and delay disclosure among pediatric patients presenting for acute and non-acute medical evaluations of sexual abuse or assault, and to examine any differences in disclosure tendencies among female adolescents and pre-adolescents. Participants and setting: A chart review of a consecutive sample of pediatric patients presenting to the emergency department or outpatient clinic identified 601 patients who were diagnosed with sexual abuse and were willing to answer examiner questions about their disclosure. Methods: Data collection included attainment of patient narratives which were utilized to gather information about abuse disclosures. Recursive abstraction was applied to categorize patient statements for further analysis, while Pearson chi square and logistic regression were utilized for quantitative data. Results: Young age (<11 years) at abuse onset was the strongest predictor of, and fear of consequences to self was the most common reason for, disclosure delay in both adolescent and pre-adolescent females. Severity of abuse, adult perpetrator, and self-blame predicted delays only in pre-adolescent females. Conclusions: Social and moral development during middle childhood likely has a strong influence on disclosure tendency. Strategies to promote disclosure should consider reducing fear of consequences associated with the adult-child paradigm.